Differential inhibition of dengue virus infection in mammalian and mosquito cells by iota-carrageenan - Talarico, L.B. (2011)
The antiviral activity against dengue virus-2 (DENV-2) of carrageenans reported here has shown a differential susceptibility of C6/36 HT and Vero cells, taken as models of mosquito and mammalian cells, depending on the structural class of polysaccharides: all polysaccharides blocked DENV-2 infection in monkey Vero cells, but only iota-carrageenans were virus inhibitors in mosquito cells. However, iota-carrageenans were less effective in mosquito cells in comparison with mammalian cells with effective concentration 50% (EC50) values in C6/36 HT cells 4.9-17.5-fold higher than in Vero cells, as determined by virus yield reduction assay. The mode of action of iota-carrageenan in both cell types was strikingly different: in Vero cells the inhibitory activity was exerted only at the initiation of the cycle, affecting virion binding, whereas in mosquito cells DENV-2 adsorption was not affected and comparable levels of inhibition were obtained if the compound was added to cells together with the virus, after 8 h of infection or by cell pretreatment before infection. Furthermore, iota-carrageenans induced a subtle alteration in mosquito cells, detected by cell proliferation and protein synthesis analyses, suggesting that a probable cellular target may be responsible for the refractory state of mosquito cells to DENV-2 infection produced by this class of polysulfates. The failure of iota-carrageenan to block DENV-2 adsorption to mosquito cells appeared to be related to the low presence of adequate heparin sulfate (HS) in C6/36 HT cell surface and is indicative of a differential participation of HS residues for DENV-2 entry in both types of cells. © 2011 SGM.